Multiplicative thinking: Much more than knowing multiplication facts and procedures - Hurst, Chris; Hurrell, D. (Australian Asssociation of Mathematics Teachers, 2016)
Using examples from a current Year 6 research project, this article highlights the importance of a combination of conceptual understanding and procedural fluency in developing multiplicative thinkers.